Epiphytology and control of Phytophthora infestans the late blight fungus, on tomato plants - Maschio, Lucila M. de A.; Sampaio, Ivan B.M. (Pesquisa Agropecuaria Brasileira, 2014)
To predict and control Phytophthora infestans in tomato (Lycopersicon esculentum Mill.), all analysis was made of the regression between the degree of infection and important macroclimatic phenomena of the humid temperate region of Colombo. PR. The following equation, with good forecasting potential, appropriate to the local production system, was discovered: Y = - 0,8671 + 0,0209 X1X2, where during a sequence of ten days, Y represents the degree of infection. and X1X2 the sum of the number of rains equal or greater than 0.1 mm time the number of night time temperatures equal to or greater than 10ºC. It was found that the sum of X1X2 equal to 40 indicates the approach of an epiphyte. It was therefore determined that the application of fungicides should be made whenever X1X2 reaches the value of 40. Field trials proved epiphyte control using the equation presented above.